Manipulations in the mycoparasite application techniques against Rhizoctonia root rot of cotton - and VINOD SINGH, R.B. GAUR, R.N. SHARMA (Indian Phytopathology, 2005)
Green house and multilocational field studies were conducted (1999-2002) to evolve the best application technique of Trichoderma harzianum for controlling dry root rot (Rhizoctonia bataticola) of cotton (Gossypium arboreum). Field studies conducted on the basis of preliminary green house results conclusively proved that dry root rot of cotton can be effectively and economically managed by the soil application of 10- 15 days pre incubated T. harzianum (TG-l) @ 10 kg ha-1 in 200 kg of Farm yard manure followed by the practice of seed treatment with T. harzianum @ 10 g kg- 1 seed in combination with soil application of ZnS04 @ 25 kg ha- 1 . Under preliminary green house studies practice of pre incubating Trichoderma in FYM before soil application proved significantly superior than alone application of bioagent. Wheat bran based formulation of Trichoderma gave better control of disease than talc based formulation for. soil application. Similarly technique of soil application of Trichoderma was found significantly superior over seed treatment. Technique of seed dip, solid matrix priming and integration of â€œmothâ€ intercropping did not prove effective.